EXPLORING NOUN MODIFIERS: A SEMANTIC ANALYSIS OF SINGULAR AND PLURAL FORMS - Norhafizan Awang; Mirrah Diyana Maznun; Siti Anisah Mohd Hatta; Norlida Razali, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study is an attempt to investigate the functional deployment of an English grammatical subsystem, the noun modifier. Underlying this study is a presumption that the rule on noun modifiers from the traditional approach has not been comprehensive enough. The rule states that noun modifiers should be in singular form. This needs verification and therefore it is necessary to find out whether the plural form exists. This study was carried out using the meaning-based framework proposed by two Columbia School advocates; Reid (2011) and Tobin (1990). The research objectives and questions in this study necessitated the use of a textual analysis format. The data were gathered from 100 journalistic articles from The Economist. Data were analysed by computing all occurrences of noun modifiers - both singular and plural - and were quantified using SPSS software (21.0). Simple descriptive statistics were used to carry out data analysis. The main concern of this study was to assess the validity of the conventional noun modifier rule, by examining its occurrence in actual context of English language use. The results reveal that noun modifiers are not always singular; in other words there are occurrences of plural nouns in actual language use. Based on Reid’s Entity Number System, it was postulated that whenever the suffix -s is added to a noun modifier, the writer intended to signal MORE THAN ONE meaning. The findings point to an unassailable feature of the choice of the noun modifiers: each grammatical feature is chosen for its semantic value independently contributing to communication.